Economic history : made simple - Smales, Bernard J. (Made Simple Books : Heinemann, 1981)
Economic History: Made Simple traces Great Britain's economic history starting from about 1760 onwards. It also assesses the impact of technological change on people's lives. The book is organized into four sections covering different periods. Section I deals with emergence of the first industrial nation from 1760-1830. Section II focuses on the 1830-1914 period, when Britain was undergoing the transition from being a primarily agricultural and commercial economy into the first modern industrial state in the world. Section III discusses the 1914-39 period, which saw the First World War, follow.